PRODUKSI SIKLODEKSTRIN DARI PATI GARUT MENGGUNAKAN BERBAGAI KOMBINASI ENZIM [Production of Cyclodextrin from Arrowroot Starch by Using the Combination Enzymes] - Erliza Noor; Liesbetini Hartoto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
The research was aimed to produce cyclodextrin from arrowroot starch using a combination of starch hydrolysis enzymes (a-amylase, b-amylase, pullulanase and glucoamylase). Cyclization process to form cyclodextrin was obtained using Cyclodextrin-glycosyl-transferase (CGTase). a-amylase showed better performance and faster to hydrolyze arrowroot starch as compared to that of β-amylase. Glucoamylase also was gave better result than pullulanase to break the α-1,6-glycosidic chain. Combination of α-amylase and glucoamylase were more efficient for hydrolysis process and cyclodextrin production.